Formação de professores: a aprendizagem baseada em problemas e sua contribuição para o desempenho do professor na sala de aula - ROSÁRIO, Daísa Gomes do (2005)
The Problem Based Learning (PBL) has been indicated out as an important tool to teach the students how to learn by themselves. The aim of the present work is to investigate under which way PBL may contribute to the formation of teachers both for the High School and Higher Education. In order to reach this objective we delivered a PBL based holiday course dedicated to re-discover the functional anatomy of animals with contrasting life styles. Teachers and students of the High School as well as Higher Education students of Biology and Medicine were subjects of the investigation. Quali-quantitative analysis were done applying questionnaires and semi-structured interviews to the teachers and students. The results revealed that PBL contributes to the formation of the reflexive teachers and increses motivation of both students and teachers at the holiday courses, suggesting that it is possible to start with PBL methodology at the High Schools and High Education in the Amazon Region, despite the present infrastructure limitations.